Kontribusi Efikasi Diri dan Dukungan Sosial terhadap Literasi Media untuk Kesejahteraan pada Pemustaka Perpustakaan Desa Berbasis Inklusi Sosial di Perpustakaan Khasanah Ilmu - Nurul Lathiffah; Kamsih Astuti (Kementerian Koordinator Bidang Pembangunan Manusia dan Kebudayaan Republik Indonesia, 2021)
Ideally, the media literacy of village library users is in the high category, so that social inclusion-based village library users can use the internet to improve welfare. In Gunungkidul Regency, there is not much media literacy for welfare in the framework of social inclusion-based libraries. Practically, media literacy for well-being is still interesting to research. This study aims to: 1) determine the relationship between self-efficacy and media literacy for the welfare of users; 2) determine the relationship between social support and media literacy for the welfare of users; 3) determine the relationship between self-efficacy and social support on media literacy for the welfare of users. In addition, this study also aims to provide advice to policy makers in terms of optimizing village libraries based on social inclusion for welfare. This study involved 74 subjects consisting of users who no longer took formal education, and worked as farmers (35 subjects), traders (5 subjects), housewives (28 subjects), and laborers (10 subjects). The researcher used purposive sampling technique and Likert scale of self-efficacy, social support, and media literacy. The data collected were analyzed using the product moment correlation. This study found that self-efficacy and social support contributed to media literacy in village library users based on social inclusion by 0.588.